Spirituality and music education: perspectives from three continents - Boyce-Tillman, June (Music and spirituality, 2017)
This book is the product of a long journey by a company of academics and practitioners sharing a common interest, titled the Spirituality and Music Education Group (SAME). It started at the International Society for Music Education Conference in Bologna in 2008, with its first gathering in Birmingham in 2010. This book is a product of the various meetings of this group. Since the group formed, the notion of spirituality has been struggling to find a way through the dominant ideology of secularisation in the West to a place in a post-secularising world. This book concentrates on examining this issue from the position of music educators on three continents. This process can be defined as both separate from as well as part of the dominant Christian and humanist traditions, whatever is appropriate in a particular culture. The book represents a fascinating array of lenses through which to examine the many and complex strands within the concept of spirituality. - Back cover